Importance of selected genetic determinants on endurance performance and physical strength: a narrative review - Yao, Jiawei; Saraf, Falguni; Rathore, Vishan Singh; Darkazanli, Kinan; Liu, Yubo; Korivi, Mallikarjuna; Bhaskar, L. V. K. S. (Frontiers in Physiology, 2025)
Physical strength and endurance of an individual are vital for athletic performance, and minimizing the risk of injuries, especially during competitions. Other than training and diet, athletic performance is determined by genetic factors or heredity, which is less focused in sports science research. Genetic factors play a crucial role in greater cardiovascular endurance and muscular phenotypes, and thereby contribute to athletic success. Several genes and different polymorphisms are positively/negatively associated with athletic performance. This review delved into the intricate role of several genes and polymorphisms in different-population groups, and explored their impact on an individual’s ability to engage in athletic activities. Among several identified genes, the prominent genes, including ACE, AGT, BDKRB2, NOS3, HIF1A, ACTN3, AMPD1, PPARGC1, SOD2, BDNF, VDR and mtDNA are discussed in this study. These genes have been reported to play indispensable roles in endurance performance and power. Furthermore, genetic variations/polymorphisms within these genes are potential to impact various aspects of physiology, including cardiovascular function, muscle fiber composition, and metabolic efficiency. Genetic polymorphisms are recognized as contributing factors in determining the athletic capacity to engage and perform sustained physical activities in their respective sports. We emphasized the noteworthy discoveries from the existing literature, and precisely explored the association between particular gene polymorphisms and athletic prowess, with a specific focus on endurance-oriented sports (running, cycling, and swimming) and power sports. Understanding the genetic variations and their influence on endurance/power sports can offer valuable insights for athletes, coaches, and scientists in sports sciences, who strive to enhance athletic training strategies and performance outcomes in achieving success.